Self-nanoemulsifying Drug Delivery System of Cilnidipine - Rao, Monica Raghavendra Prasad; Kulkarni, Sayali; Sonawane, Ashwini; Sugaonkar, Sayali (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Self-nanoemulsifying Drug Delivery Systems (SNEDDS) are physically stable, isotropic mixtures of oil, surfactant and co-surfactant. The turbulence generated by peristaltic movements of the GIT causes formation of oil-in-water (o/w) nano-emulsions upon dilution. The objective of this study was to improve solubility and oral bioavailability of Cilnidipine by formulating liquid-SNEDDS. Materials and methods: Capmul PG8 NF, Cremophor RH40, and Transcutol HP were selected as oil, surfactant, and co-surfactant. Ternary phase diagrams were constructed to evaluate the nanoemulsification region. A 32 factorial design was employed to optimize L-SNEDDS with droplet size and drug release as responses. SNEDDS of CLN was evaluated for droplet size, self-emulsification time, in vitro drug release, ex-vivo permeation, pharmacokinetics and tissue distribution studies and stability studies. The optimized L-SNEDDS was converted into solid form using β-cyclodextrin nanosponges as adsorbents and evaluated in terms of micromeritics, drug content, scanning electron microscopy and powder X-ray diffraction. Results: The optimized batch exhibited droplet size of 23.70 nm, and in vitro drug release of 95.24 % in 60 min.The in-vivo studies revealed nearly 5.53 folds increase in AUC0-∞ of optimized batch of liquid SNEDDS compared to CLN which can be credited to increase in solubility and dissolution rate. Conclusion: In vivo studies revealed improved pharmacokinetic properties which were attributed to greater surface area and lymphatic absorption leading to circumvention of hepatic first pass metabolism.
Keywords: Cilnidipine; 32 factorial designs; Nanosponges; solid SNEDDS; Oral bioavailability